A Non-Standard Characteristic Based Protection Scheme for Distribution Networks - Kilickiran, Hasan Can; Akdemir, Huseyin; Sengor, Ibrahim; Kekezoglu, Bedri; Paterakis, Nikolaos G. (MDPI, 2018)
The increasing number of distributed generation (DG) units in the distribution systems poses a challenge on protection systems in terms of coordination. In addition, the single characteristic based conventional protection causes an increase in the primary operation time of the relays due to the coordination between relay pairs. As a consequence, earlier studies investigated the utilization of non-standard characteristics and protection schemes in order to ease the insufficiencies of the standard approach. However, a commonly accepted protection approach that mitigates the effect of DG while providing lower primary operating time by levering the benefits of the non-standard protection strategy has not been developed so far. In order to overcome the aforementioned drawbacks of traditional protection, this paper firstly introduces a non-standard characteristic and then proffers an unconventional protection strategy, which utilizes a double characteristic. The suggested protection approach is tested on the IEEE 14 Bus distribution system including synchronous generator based DG connection. The results show that the proposed characteristic and protection scheme are able to provide a substantial decrease in the operation time of the relays while meeting the coordination requirements.
Keywords: digital relay; non-standard characteristic; non-standard curve; protection; unconventional relay characteristic; OVERCURRENT RELAYS; DISTRIBUTION-SYSTEMS; COORDINATION; GENERATION; Energy & Fuels